2013
DOI: 10.1007/s12013-013-9810-6
|View full text |Cite
|
Sign up to set email alerts
|

The Injurious Effects of Hyperinsulinism on Blood Vessels

Abstract: Insulin resistance (IR) is a common feature of hypertension, Type II diabetes, coronary heart disease, Syndrome X, and other vascular diseases. It refers to a state in which a certain concentration of insulin produces less biologic effect than expected in human body. When IR develops, the response of human body to insulin decreases accordingly, thus inducing the compensatory hyper-secretion of insulin and consequently hyperinsulinism. Many clinical and epidemiologic studies have demonstrated that IR and iatrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Insulin is the key regulator of liver glucose metabolism, but its effectiveness depends on several factors, including how it is distributed across the body. Of note, arterial hyperinsulinemia is associated with metabolic and cardiovascular disease and hypoglycemic risk and is a contributor to type 2 diabetes (2,(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin is the key regulator of liver glucose metabolism, but its effectiveness depends on several factors, including how it is distributed across the body. Of note, arterial hyperinsulinemia is associated with metabolic and cardiovascular disease and hypoglycemic risk and is a contributor to type 2 diabetes (2,(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 DM is comprised of complex metabolic disorders, including hyperglycemia, hyperlipidemia and hyperinsulinemia ( 21 ). Experimental studies have demonstrated that high concentrations of insulin may confer direct or indirect effects on amplifying cardiovascular stress ( 15 ). Abhijit et al reported that VSMCs exposed to hyperinsulinemia may exhibit increased ROS generation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Shiny et al and Martínez-Hervás et al provided evidence to suggest that hyperinsulinemia aggravates the inflammatory response and reduces VSMC survival, respectively ( 28 , 29 ). It is well documented that ROS and inflammation may induce VSMC proliferation and migration ( 15 , 27 , 28 ); however, the association between apoptosis and VSMC dysfunction remains debatable; a study has indicated that apoptosis may also trigger VSMC proliferation, leading to neointimal hyperplasia ( 30 ); however, the underlying mechanisms of this phenomenon are unclear ( 30 ). In line with previous studies, the present study indicated that stimulation with high concentration insulin promoted VSMC dysfunction and pathological injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations